A structural model of cash waqf intention among Malaysian Muslim Gen Y and Gen Z: The mediating role of attitude - Wan Rasyidah Wan Nawang; Intan Fatimah Anwar; Nurul Ain Azri (Academic Inspired Network, 2025)
Albeit various initiatives, cash waqf participation in Malaysia, particularly among younger Muslims, remains low. This study examines the factors shaping Generation Y and Z’s intention to contribute, focusing on cash waqf awareness, religiosity, perceived Ihsan, Islamic egalitarianism, and attitude, with attitude also tested as a mediator. Using purposive sampling, 208 responses were analysed via Partial Least Squares Structural Equation Modelling (PLS-SEM). Results show that awareness, religiosity, and Islamic egalitarianism significantly influence attitude, which in turn predicts intention, while perceived Ihsan showed no significant effect. Attitude also mediated the effects of awareness, religiosity, and Islamic egalitarianism on intention, but not perceived Ihsan. This study extends waqf literature by addressing an underexplored demographic and offers practical insights for waqf institutions: enhancing awareness, reinforcing religious values, and promoting Islamic principles of justice may strengthen young Muslims’ engagement with cash waqf.